Women in Post Flood Situation: A Study on Human Security of IDPs Women in Golakganj, Dhubri District, Assam (International Journal of Food and Nutritional Sciences, 2022)
The flood in Assam is such a regular feature that today hardly anyone takes a serious note of it. The state of Assam is frequently ravaged by the fury of mighty Brahmaputra and its tributaries causing untold human misery and devastation of indescribable nature. The flood situation in Assam have resulted unending sufferings and populations displacement in the region with no national or state policy to permanently solve the situations. Thus, the human security of those displaced persons living in the flood and post flood situations since decades have been very poorly addressed with no solution on unending crisis on the ground. Among the displaced populations, women and children were one of the most vulnerable groups in terms of defending their rights and security. Moreover, gender based violence is also a common occurrence. Under the pretext of this, the present study attempts to study the human security of IDPs women in the post flood situations.